Collaboration between supply chain partners: when does it matter? Evidence from collaborative profiles. Issue 6 (27th November 2020) - Kumar, Gopal
Abstract : Purpose: Considering the limitations of supply chain collaboration (SCC) literature, the purpose of this paper is to develop SCC framework and analyze the SCC practice based on the framework. The framework incorporating internal and external knowledge sharing under a collaborative culture (CC) and problem-solving environment preceded by preparedness is required. Design/methodology/approach: To achieve successful collaboration, this paper encompasses problem-solving and performance measurement, preparedness, culture, relationship strength (RS) and gives resource sharing and planning as internal and external focused perspectives. Exploratory methods are used to analyze the data from industries. Findings: CC, RS and preparedness are crucial that reflect the health of collaboration. Three levels of collaboration practice – good, moderate and weak – are prominent where the extent of SCC practice seems weak. Collaborative activities that matter more are identified. Market-based knowledge sharing is important for good and moderate SCC, while weaker collaboration does not focus on it. Interestingly, this paper finds an increasing level of collaboration may not always result in increased performance. Firms from the pharmaceutical, automobile and electrical/electronic industry tended to practice higher collaboration as compared to other industries. Originality/value: By integrating market-driven management, resource-based view, and contingency theory, the SCC framework gives a new perspective. Joint planning and resource sharing are categorized as internal and external focused functional areas. The paper identifies three profiles of collaboration and discusses the importance of SCC activities in achieving performance.